Representation of Beauty in Somethinc Advertisements: A Critical Discourse Analysis of Norman Fairclough on Instagram Social Media - Anindya Destyn Wahyuningtyas; Eka Yuli Jayanti (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2026)
The development of social media platforms, especially Instagram, has become a strategic place for the beauty industry to promote products and establish new beauty standards. This study aims to examine the image of beauty in Somethinc advertisements on Instagram using Norman Fairclough's Critical Discourse Analysis approach and Stuart Hall's representation. The method used in this study is descriptive qualitative with three stages of analysis, namely text analysis, discursive practice, and social practice. Data were obtained through documentation of Somethinc advertisement screenshots and analyzed narratively. The results of the study show that the Calm Down Skinpair R-Cover Cream advertisement emphasizes the emotional aspect with the slogan "NEVER SETTLE for LESS!", while the Skinlift Serum advertisement emphasizes scientific claims such as "Flaw fine lines & wrinkles" and dermatological certification. Both advertisements reinforce the ideal image of beauty that includes healthy, bright, and flawless skin, and connect product use with identity and confidence. The conclusion of this study emphasizes that Somethinc advertisements not only function as promotional tools, but also as a medium for shaping beauty ideologies among teenagers and young women..